Enhanced activity of Ru-Ir nanoparticles over SiC for hydrogenation of levulinic acid at room-temperature. (March 2021) - Wang, Jingru; Zhu, Shanhui; Wang, Yunwei; Wang, Yingyong; Jin, Guoqiang; Tong, Xili; Guo, Xiangyun
Graphical abstract: A highly efficient Ru-Ir bimetallic catalyst supported on SiC for the aqueous hydrogenation of levulinic acid (LA) into γ-valerolactone (GVL) under mild conditions. The enhanced catalytic activity of Ru0.5 -Ir2.5 /SiC originates from the electronic synergistic effect among Ru, Ir and SiC. Highlights: SiC supported Ru-Ir catalysts were synthesized by wet impregnation method and characterized. High yield of 100 % for GVL were achieved under mild condition. The synergistic effect among Ru, Ir and SiC makes Ir nanoparticles electron-rich. The dissociated hydrogen from Ir particles spills over to the SiC surface and reacts with LA adsorbed on SiC to GVL. Abstract: The hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) under mild condition is a promising but challenging process. Herein, SiC supported Ru-Ir bimetallic catalyst exhibit enhanced catalytic activity for aqueous hydrogenation of LA into GVL under mild conditions. Comparing with monometallic Ir3 /SiC and Ru3 /SiC, the conversion of LA over bimetallic Ru0.5 -Ir2.5 /SiC catalyst increase from 51.2 % and 45.9% to 100% at 25 °C and 0.2 MPa of H2 pressure. The enhanced catalytic activity of Ru0.5 -Ir2.5 /SiC catalyst originates from the electronic synergistic effect among Ru, Ir and SiC. Due to the electron transfer, electron-richened Ir nanoparticles show stronger ability for H2 dissociation, and the SiC surface produces more active sites to accommodate hydrogen species that spill over from Ir and Ru. The adsorption and hydrogenation of LA molecules occur on the surface of SiC.